Urban environment during early-life and blood pressure in young children. (January 2021) - Warembourg, Charline; Nieuwenhuijsen, Mark; Ballester, Ferran; de Castro, Montserrat; Chatzi, Leda; Esplugues, Ana; Heude, Barbara; Maitre, Léa; McEachan, Rosemary; Robinson, Oliver; Slama, Rémy; Sunyer, Jordi; et al.
Highlights: Environmental stressors in urban settings are multiple. Exposure to air pollution during early life was associated with higher blood pressure. Ambient temperature was inversely associated with blood pressure in children. Noise, SES-area level, and features of the built environment were also predictors of blood pressure. Designing cities that promote healthy environments is of high importance. Abstract: Background: The urban environment is characterised by many exposures that may influence hypertension development from early life onwards, but there is no systematic evaluation of their impact on child blood pressure (BP). Methods: Systolic and diastolic blood pressure were measured in 4, 279 children aged 4–5 years from a multi-centre European cohort (France, Greece, Spain, and UK). Urban environment exposures were estimated during pregnancy and childhood, including air pollution, built environment, natural spaces, traffic, noise, meteorology, and socioeconomic deprivation index. Single- and multiple-exposure linear regression models and a cluster analysis were carried out. Results: In multiple exposure models, higher child BP, in particular diastolic BP, was observed in association with higher exposure to air pollution, noise and ambient temperature during pregnancy, and with higher exposure to air pollution and higher building density during childhood (e.g., mean change [95% confidence interval] for an interquartile range increase in prenatal NO2  = 0.7 mmHg[0.3;1.2]). Lower BP was observed in association with higher temperature and better street connectivity during childhood (e.g., temperature = -1.1[-1.6;-0.6]). Some of these associations were not robust in the sensitivity analyses. Mother-child pairs were grouped into six urban environment exposure clusters. Compared to the cluster representing the least harmful urban environment, the two clusters representing the most harmful environment (high in air pollution, traffic, noise, and low in green space) were both associated with higher diastolic BP (1.3[0.1;2.6] and 1.5[0.5;2.5]). Conclusion: This first large systematic study suggests that living in a harmful urban environment may impact BP regulation in children. These findings reinforce the importance of designing cities that promote healthy environments to reduce long-term risk of hypertension and other cardiovascular diseases.